O uso de antibióticos e seu impacto na microbiota: efeitos na asma alérgica experimental - Gregório Grama Cavalcante (2018)
Asthma is a disease that affects about 300 million people. It consists of reversible bronchial obstruction and inflammation of the pulmonary parenchyma. Frequent use of antimicrobials could cause dysbiosis and may be implicated in changes in the immune response in the asthmatic disease. To investigate this potential impact, 21-day old BALB/cAnNCrl mice were treated with amoxicillin, trimethoprim/sulfamethoxazole, azithromycin or metronidazole at therapeutic doses for 3 cycles of 7 days (3 days for azithromycin) with a 7-day recovery period. One group received only water throughout the experiment as untreated control group. In parallel, the mice were sensitized i.p with OVA + Alum to develop allergy, while some animals received only Alum as non-allergic controls. After the end of the recovery period, the mice were challenged with aerosolized OVA for asthma induction. Forty-eight hours after the last challenge, the animals were sacrificed and the lung parameters were evaluated and serum, lung and BAL were collected for further analysis. Feces collected during different treatment points and BAL collected during the sacrifice had their DNA extracted and sequenced to characterize the microbiota targeting the bacterial RNAr 16s gene. Asthmatic mice treated with amoxicillin and trimethoprim/sulfamethoxazole showed increased pulmonary hyperreactivity, reduced levels of serum IgG1 and higher levels of IL-4 and IL-6 in bronchoalveolar lavage compared to the asthmatic group treated with regular water. Asthmatic mice treated with azithromycin and metronidazole had a preserved FEV-50 parameter and a lower level of tissue inflammation when compared to the asthmatic animals treated with water. The metronidazole group also had higher levels of serum IgG1. Regarding the microbiome, the animals treated with amoxicillin or trimethoprim/sulfamethoxazole had a greater bacterial alpha diversity in the BAL when compared to the allergic control group. Although the intestinal microbiota recovers itself and becomes similar to the untreated control group (with the exception of the azithromycin group), the presence of microbiological "scars" are observed even after the recovery period, especially the enrichment of bacteria Blautia coccoides and Akkermansia muciniphila for the groups treated with azithromycin and metronidazole, respectively. To date, this is the first antimicrobial intervention performed at therapeutic doses demonstrating a change in the immune response caused by these drugs in allergic asthma.